The Skeleton and Biomineralization Mechanism as Part of the Innate Immune System of Stony Corals - Levy, Shani; Mass, Tali (Frontiers in Immunology, 2022)
Stony corals are among the most important calcifiers in the marine ecosystem as they form the coral reefs. Coral reefs have huge ecological importance as they constitute the most diverse marine ecosystem, providing a home to roughly a quarter of all marine species. In recent years, many studies have shed light on the mechanisms underlying the biomineralization processes in corals, as characterizing the calicoblast cell layer and genes involved in the formation of the calcium carbonate skeleton. In addition, considerable advancements have been made in the research field of coral immunity as characterizing genes involved in the immune response to pathogens and stressors, and the revealing of specialized immune cells, including their gene expression profile and phagocytosis capabilities. Yet, these two fields of corals research have never been integrated. Here, we discuss how the coral skeleton plays a role as the first line of defense. We integrate the knowledge from both fields and highlight genes and proteins that are related to biomineralization and might be involved in the innate immune response and help the coral deal with pathogens that penetrate its skeleton. In many organisms, the immune system has been tied to calcification. In humans, immune factors enhance ectopic calcification which causes severe diseases. Further investigation of coral immune genes which are involved in skeleton defense as well as in biomineralization might shed light on our understanding of the correlation and the interaction of both processes as well as reveal novel comprehension of how immune factors enhance calcification.